2001
DOI: 10.1155/2001/25301
|View full text |Cite
|
Sign up to set email alerts
|

Development of lntraepithelial Cellsin the Porcine Small Intestine

Abstract: The number, phenotype, localisation and development of intraepithelial lymphocytes (IEL) from duodenum (Du) and ileum (I1) were studied by immunohistochemistry (IHC) and light and electron microscopy in unweaned (0-7 weeks old) and six months-old pigs. Developmental changes at birth showed that 38% of the total lymphocytes in the villi were IEL, mainly of the CD2+CD4-CD8-double negative (DN) phenotype. That proportion rose to over 50% at week 5 after birth, resembling adult proportion, although still with fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…IEL are Tlymphocytes, mainly of the CD8 + phenotype, of which the functions have not been entirely elucidated. It is accepted that they play a central role as a first line of defence against foreign luminal antigens (pathogens, proteins), in the induction of apoptosis of epithelial cells and in the conservation of the mucosal integrity (Vega-Lopez et al 2001). This is in line with the observations of Czernichow et al (1996) showing that enterally infused MCTAG enhanced mucosal mass and favoured epithelial cell renewal in the proximal intestine in rats.…”
Section: Efficacy In the Fieldsupporting
confidence: 63%
“…IEL are Tlymphocytes, mainly of the CD8 + phenotype, of which the functions have not been entirely elucidated. It is accepted that they play a central role as a first line of defence against foreign luminal antigens (pathogens, proteins), in the induction of apoptosis of epithelial cells and in the conservation of the mucosal integrity (Vega-Lopez et al 2001). This is in line with the observations of Czernichow et al (1996) showing that enterally infused MCTAG enhanced mucosal mass and favoured epithelial cell renewal in the proximal intestine in rats.…”
Section: Efficacy In the Fieldsupporting
confidence: 63%
“…Vega-Lopez et al (2001) observed similar developmental changes in IEL and proposed that the delayed maturation of IEL might be positively correlated with the increased disease susceptibility of young pigs. Even though there is more to learn about IEL, particularly in domestic animal species, their location among the intestinal epithelia is indicative of their importance as immune regulators and effectors at the luminal-epithelial interface.…”
Section: Galt Effector Sitesmentioning
confidence: 69%
“…However, these studies differ from ours in a number of respects since piglets were challenged with virulent strain LT2 8 days after the protective inoculation, whereas the effect that we report here occurred within 48 h after challenge. Although numerous studies have shown that enterocyte pathology is associated with Th1 cytokines, such as gamma interferon and tumor necrosis factor alpha (TNF-␣) (1,17,21,36), insignificant numbers of lymphocytes are found in the intestines of gnotobiotic piglets (29,42). This may indicate that within the first week after birth (the duration of our study) the production of inflammatory cytokines is not sufficient to induce the severe pathology that we observed in F98-infected piglets.…”
Section: Discussionmentioning
confidence: 60%